Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.jnoncrysol.2016.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive study on physical, elastic and shielding properties of lead zinc phosphate glasses

Abstract: A series of ternary phosphate glasses in the form of (PbO)x(ZnO)60-x(P2O5)40 where x = 0-60 mol%, have been successfully prepared by conventional melt-quenching technique. The physical and elastic properties of the glasses have been investigated using pulse echo technique. The longitudinal and shear velocity of the glasses were measured using the MBS8000 ultrasonic data acquisition system at 10 MHz frequency in room temperature. The density, ultrasonic velocity and elastic moduli are found to be composition de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(13 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The buildup factors for exposure (EBF) and absorbance (EABF) of the fabricated new glasses are calculated using the methods of interpolation from the equivalent atomic number Z eq . Calculations are divided into three steps 38–40 :…”
Section: Methodsmentioning
confidence: 99%
“…The buildup factors for exposure (EBF) and absorbance (EABF) of the fabricated new glasses are calculated using the methods of interpolation from the equivalent atomic number Z eq . Calculations are divided into three steps 38–40 :…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the significant use of x-ray and gamma-ray in many fields requires hard efforts to search for new materials which are economic, environment friendly, and proper protective against x-ray and gamma-ray. In this regards, several authors reported different type of glasses as promising shielding materials [7][8][9][10][11]. Sayyed [7] proposed some HMO glasses such as PbO, MgO, Ag 2 O, Nb 2 O 5 , ZnO and BaO for gamma-ray applications.…”
Section: Introductionmentioning
confidence: 99%
“…The results were compared with some concretes. Phosphate glasses were also studied and it was noted that the substitution of ZnO by PbO improves the gamma-ray shielding ability of the glasses [11]. However, the toxicity the lead (Pb) provide strong motivations to replace Pb element by another high-Z element such as Mo, Ba, W, Bi, Gd and etc.…”
Section: Introductionmentioning
confidence: 99%
“…Decrease in both and with the rise of ZnO also indicates that the ultrasonic wave encounters more resistance in the ZnO-SiO 2 samples as the amount of ZnO increases [27,28]. Not only that, rise of ZnO in the ZnO-SiO 2 samples also indicates that more Zn 2+ ions exist in the samples and this caused overall more ions in samples to be opened up [29]. A result of lower ultrasonic velocity at higher content of ZnO indicates a major alteration in the structures of the samples.…”
Section: +mentioning
confidence: 96%